Splendid Land, Splendid People : The Chickasaw Indians to Removal - Atkinson, James R. (Book collections on Project MUSE., 2004)
Before the Chickasaws were removed to lands in Oklahoma in the 1800s, the heart of the Chickasaw Nation was located east of the Mississippi River in the upper watershed of the Tombigbee River in what is today northeastern Mississippi. Their lands had been called ""splendid and fertile"" by French governor Bienville at the time they were being coveted by early European settlers. The people were also termed ""splendid"" and described by documents of the 1700s as ""tall, well made, and of an unparalleled courage. ... The men have regular features, well shaped and neatly dressed; they a.